Crossmodal spatial attention. - Spence, C (2010)
In this review, I highlight some of the most exciting recent developments in the area of crossmodal spatial attention, focusing on studies that question the automaticity of exogenous spatial orienting following the peripheral presentation of spatially uninformative unimodal cues. The latest research, showing that multisensory cues capture participants' spatial attention more effectively than unimodal cues, is also reviewed. There has been a rapid growth of interest in the application of laboratory-based studies of crossmodal attention to real-world interface design, and this research is discussed, focusing, in particular, on the design of multisensory warning signals for drivers. Finally, I outline a number of key issues for future applied research in the study of crossmodal exogenous spatial attention.